Pengembangan Game Education Unjumble Untuk Meningkatkan Kemampuan Bahasa Anak Pada Kelompok B di PAUD Alif Monjok - Alpina Purwita Sari; Gunawan Gunawan; Baik Nilawati Astini; Nurhasanah Nurhasanah (Indonesian Journal of Elementary and Childhood Education, 2024)
This research aims to produce educational games that are feasible, practical and effective. The research and development method uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data collection was carried out through observation, interviews, documentation and questionnaires with media experts, material experts and teachers. Data analysis was carried out descriptively, quantitatively and qualitatively. The results of stage I media expert validation showed a percentage of 72.5%, and in stage II it increased to 90%, indicating an increase in the feasibility of the game. Material expert validation in stage I showed a percentage of 96.4%, stage II 92.8%, and stage III 91%, showing consistency in the suitability of the material. The results of the practicality test by the teacher showed a percentage of 75%. Observations of children show an increase in language skills, especially in the aspect of increased language skills and aspects of composing words, from stage I of (71.9) to stage II of (81.5) so it can be said to be very effective for implementation in group B children at PAUD Alif. The educational game Unjumble has proven to be feasible, practical and effective in improving the reading language skills of group B children, especially in the aspect of composing words, becoming a fun and interactive alternative learning media. The implication for this research is to add other media or safety toys to conduct conditions in the classroom when the research is carried out.